THE OPERATIONAL RELIABILITY OF THE DISC OF PORCELAIN INSULATORS THE CONTACT NETWORK. PREDICTION RESIDUAL LIFETIME - Kim, En Dar; Taran, V. M.; Sychenko, V. H. (Science and Transport Progress, 2006)
The method of estimation of reliability of porcelain insulators is described in the article.